Cordyceps militaris extracts and cordycepin ameliorate type 2 diabetes mellitus by modulating the gut microbiota and metabolites - Liu, Xinyuan; Dun, Mengqian; Jian, Tongtong; Sun, Yuqing; Wang, Mingyu; Zhang, Guoying; Ling, Jianya (Frontiers in Pharmacology, 2023)
Cordyceps militaris, which has many potential medicinal properties, has rarely been reported to alleviate type 2 diabetes mellitus (T2DM). The effects of C. militaris extracts (CE) and cordycepin (CCS) on high-fat diet and streptozotocin (STZ) induced T2DM mice were analysed by gut microbiome and metabolomics methods in this study. The results demonstrated that glucose and lipid metabolism parameters, oxidative stress biomarkers and inflammation cytokines were down-regulated in the CCS and CE groups. A comparative analysis of the fecal samples from mice in the model and experimental groups showed that experimental groups resulted in a higher abundance of Firmicutes/Bacteroidetes. This study provides evidence that C. militaris can be used as a food supplement to relieve T2DM, which provides a promising prospect for new functional food in it.